2015
DOI: 10.9714/psac.2015.17.1.010
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer monitoring between quenched high-temperature superconducting coated conductors and liquid nitrogen

Abstract: High-temperature superconducting coated conductors (HTS-CCs) are good candidates for resistive superconducting fault current limiter (RSFCL) applications. However, the high current density they can carry and their low thermal diffusivity expose them to the risk of thermal instability. In order to find the best compromise between stability and cost, it is important to study the heat transfer between HTS-CCs and the liquid nitrogen (LN 2 ) bath. This paper presents an experimental method to monitor in real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…During the limitation event, the SCFCL experiences electric current and voltage simultaneously and thus a large amount of heat is generated. The conduction of the heat through the interface CC tape/LN2 is very poor, because LN2 evaporates due to a high temperature difference in the solid-liquid interface, and forms a vapour film with thermally insulating properties [5][6][7][8]. Roy et al [9] showed by means of modelling of HTS tapes for resistive type of SCFCL, that the key factor in success to readily attain the thermal stability is the heat capacity instead of thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…During the limitation event, the SCFCL experiences electric current and voltage simultaneously and thus a large amount of heat is generated. The conduction of the heat through the interface CC tape/LN2 is very poor, because LN2 evaporates due to a high temperature difference in the solid-liquid interface, and forms a vapour film with thermally insulating properties [5][6][7][8]. Roy et al [9] showed by means of modelling of HTS tapes for resistive type of SCFCL, that the key factor in success to readily attain the thermal stability is the heat capacity instead of thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…By varying thpol, the temperature difference between the dissipating parts and the liquid nitrogen during a fault can be adjusted. However, this thickness cannot be increased indefinitely, as this may greatly increase the recovery time tr after the fault is isolated [21].…”
Section: B Copper Thickness Design (In Case Of a Fault)mentioning
confidence: 99%
“…It has been previously shown that a thin layer of insulator between an HTS tape and a cooling bath can influence the heat transfer properties [24,25]. Therefore, the presence of a fluorescent coating may have to be kept in mind when interpreting measurement results about the dynamics of the quench.…”
Section: Sample Preparationmentioning
confidence: 99%